PENGARUH KUALITAS JASA PELAYANAN DAN KUALITAS JASA CETAK TERHADAP KEPUASAN PELANGGAN - Sukartaatmadja, Iswandi; Rifqy, Dihya Nur (Jurnal Ilmiah Manajemen Kesatuan, 2015)
This research is aimed at investigating the effect of service quality on consumers ' satisfaction. Using quantitative approach as the method, there are 100 respondents in this research. There are two independent variables and one dependent variable. First independent variable is service quality and second independent variable is printing quality and the dependent variable is customer satisfaction. This research uses multiple regression linear method. The equation of the regression is Y=2,089+0,323+0,466. First independent variable 's value is 3,917 and the second Independent variable 's value is 4,465 which means there are positive and significant effect for customer satisfaction. Simultaneous hypothesis and partial hypothesis tests show significant and positive results from the independent variables to dependent variable. Keyword: Service Quality and Printing Quality to Customer Satisfaction